Ethnomedicinal plants used by Manobo Tribe in Ugnop Cave Landscape Forest Reserve, Agusan del Sur, Philippines - LYN D. PARAGUISON; JULIUS JOHN DP. SALAMANES; MARK LLOYD G. DAPAR; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2024)
Abstract. Paraguison LD, Salamanes JJDP, Dapar MLG, Alejandro GJD. 2024. Ethnomedicinal plants used by Manobo Tribe in Ugnop Cave Landscape Forest Reserve, Agusan del Sur, Philippines. Biodiversitas 25: 4223-4232. As a protected and conserved area, Upland Prosperidad in Agusan del Sur, harbors medicinal plants traditionally used by local communities and indigenous groups. This study investigates the ethnomedicinal practices of the Manobo tribe in the Ugnop Cave Landscape Forest Reserve, Prosperidad, Agusan del Sur. Data were gathered through semi-structured interviews, guided field walks, and focus group discussions with 150 key informants. A total of 57 medicinal plants, belonging to 31 families and 49 genera, were documented for their use in treating various diseases and ailments. The Fabaceae family dominated with five species reported for medicinal use. Piperaceae (FIV=98.67) and Asteraceae (FIV=96.66) were identified as the families with the highest Family Importance Value, receiving the most citation reports from key informants. The most frequently reported plant species was Piper aduncum L., traditionally used for treating cuts and wounds. Leaves were the most commonly used plant part, constituting 32% of usage. Decoction was the most common mode of preparation (55%), followed by poultice (22%) and direct eating (16%). The forest reserve was found to be rich in medicinal plant knowledge and resources among the locals and indigenous communities, emphasizing the need for ongoing protection and conservation of these valuable genetic resources.